Model-Based Dynamic Structural Modification of Machine Tools - Mateusz Wąsik; Krzysztof Lis; Krzysztof Lehrich; Łukasz Mucha (Shock and Vibration)
The article proposes modification of machine tool structures methodology on the example of a body of vertical milling centre stand. It is based on the results of experimental research and allows for the prediction of dynamic features of individual bodies and complete structures on the basis of the described modal model. It takes into account the possibility of mass change at the model node and the introduction of additional rigidity and damping by a combination of selected nodes of the model. The methodology can be applied in the case of machine tools in which the loss of stability has been found during its maintenance, what consequently disables the possibility of machining with the required machining parameters from the performance point of view. Modal parameters modification is based on structural dynamic modification techniques and preliminary simulation tests performed by using Finite Element Method (FEM) and verification with experimental research.